Geometry optimization of a magnetorheological clutch operated by coils. (February 2017) - Bucchi, Francesco; Forte, Paola; Frendo, Francesco
Magnetorheological fluids are smart materials responsive to magnetic field, widely applied in dampers and shock absorbers but also in clutches and brakes. The magnetorheological fluid gap shape is a very important topic in the design of clutches, since it directly influences the transmissible torque and the power loss. In this paper, an approach to magnetorheological fluid clutch design based on optimization is proposed and tested on four different layouts. Starting from a given available volume, two magnetorheological fluid gap shapes, namely single cylinder and multi-disc, and two coils positions, i.e. internal or external, were considered. A lumped parameter model was developed to analytically compute the magnetic flux along the clutch magnetic circuit and to calculate the transmissible torque of the clutch. The optimal geometry of the clutch for maximum transmissible torque, in terms of number and dimensions of the coil sectors, was determined for each shape and coil configuration and the results were validated by finite element models.